Empowering Rural Revitalization: Integrated Development of Rural Industries Driven by E-commerce and Empirical Analysis - Zhu, Tong; Rozan, Mohd Zaidi Abd (International Journal of Economics and Financial Issues, 2025)
With the rapid development of the digital economy, e-commerce has become a key driver in promoting rural industrial integration and economic growth. This study constructs a theoretical framework to analyze the coupling and coordination relationships among e-commerce, specialty agriculture, and rural tourism, aiming to explore their synergistic effects on rural revitalization. Based on a comprehensive evaluation index system, this research applies the entropy weight method and the coupling coordination degree model to assess the integration dynamics of these three industries. Using panel data from 2013 to 2023, the study reveals the evolving interconnections between e-commerce and rural industries. Results show that integration has significantly improved, with e-commerce playing a central role in optimizing rural structures. Specifically, the coupling degree between e-commerce and rural tourism is found to be higher than that between e-commerce and specialty agriculture, highlighting the role of digital platforms in expanding rural tourism markets. This research establishes a systematic approach for evaluating rural industry integration under e-commerce and provides empirical insights into rural industrial transformation. The findings offer theoretical and practical implications for policymakers and stakeholders to foster sustainable, coordinated rural development through digital innovation.